MUROTTAL THERAPY CAN OVERCOME SLEEP DISORDERS (CASE STUDY OF PERITONITIS PATIENTS) - Ilhamsyah; Adriawan, Adriawan; Yuniar, Putri (Homes Journal: Hospital Management Studies Journal, 2023)
Backgrounds: Peritonitis is inflammation of the peritoneum (serous membrane that lines the abdominal cavity and covers the abdominal viscera) is a dangerous disease that can occur in acute or chronic forms. Objective: The purpose of this study was to provide nursing care for peritonitis patients by administering murottal therapy in the ICU room of Laburan Baji General Hospital, Makassar. Method: The method used is a case study with data collection techniques through interviews, observation of physical examination and documentation. Result: Implementation of giving murotta therapy; allow the patient to sleep peacefully Conclusion: Based on the results of the evaluation of the cases carried out, it was concluded that giving murottal therapy to patients who have peritonitis with sleep pattern disturbance problems can be resolved properly.